Confirming the X-linked handedness gene as recessive, not additive: Reply to Corballis (2001) - Jones, G; Martin, M (2001)
M. C. Corballis (2001) has proposed a model for handedness that follows the unified distributional model of G. V. Jones and M. Martin (2000b) in its assumption that genetic variation relating to handedness is located only on the X chromosome but differs from the unified distributional model in its assumption that the relation between genotype and phenotype is of an additive rather than a recessive type. The accounts provided by the two models are compared for four major sets of findings. It is concluded that the empirical evidence favors the X-linked recessive model proposed by G. V. Jones and M. Martin (2000b).